Capturing disease severity in LIS1-lissencephaly reveals proteostasis dysregulation in patient-derived forebrain organoids - Zillich, Lea; Gasparotto, Matteo; Rossetti, Andrea Carlo; Fechtner, Olivia; Maillard, Camille; Hoffrichter, Anne; Zillich, Eric; Jabali, Ammar; Marsoner, Fabio; Artioli, Annasara; Wilkens, Ruven; Schroeter, Christina B.; et al. (Nature Communications, 2025)
LIS1-lissencephaly is a neurodevelopmental disorder marked by reduced cortical folding and severe neurological impairment. Although all cases result from heterozygous mutations in the LIS1 gene, patients present a broad spectrum of severity. Here, we use patient-derived forebrain organoids representing mild, moderate, and severe LIS1-lissencephaly to uncover mechanisms underlying this variability. We show that LIS1 protein levels vary across patient lines and partly correlate with clinical severity, indicating mutation-specific effects on protein function. Integrated morphological, transcriptomic, and proteomic analyses reveal progressive changes in neural progenitor homeostasis and neurogenesis that scale with severity. Mechanistically, microtubule destabilization disrupts cell-cell junctions and impairs WNT signaling, and defects in protein homeostasis, causing stress from misfolded proteins, emerge as key severity-linked pathways. Pharmacological inhibition of mTORC1 partially rescues these defects. Our findings demonstrate that patient-derived organoids can model disease severity, enabling mechanistic dissection and guiding targeted strategies in neurodevelopmental disorders.
Gesehen am 08.01.2026